2023
DOI: 10.56444/mem.v38i1.3374
|View full text |Cite
|
Sign up to set email alerts
|

Digital Customer Protection: Mediator between Mobile Money Usage and Financial Inclusion

Abstract: The development of technology in the 5.0 era, marked by the increase in internet usage, currently impacts people's habits in accessing financial services, such as mobile money usage. Therefore, it aligns with the government's vision to increase financial inclusion through mobile money usage to reduce poverty. However, Yogyakarta Province is a province with a poverty rate that exceeds the national average, and it is the highest in the Java region. In this regard, digital customer protection needs to be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…Researchers concluded that widespread use of mobile money services and digital payment methods could significantly impact Africa's ability to achieve its sustainable development goals and expand access to financial services. Budiyono and Sukamulja (2023) found a direct correlation between the utilisation of mobile money and the safeguarding of digital customers. This implies that a rise in the adoption of mobile money by the working-age population in Yogyakarta's Special Region will lead to enhanced security for these clients.…”
Section: Mobile Money Services and Financial Inclusionmentioning
confidence: 92%
“…Researchers concluded that widespread use of mobile money services and digital payment methods could significantly impact Africa's ability to achieve its sustainable development goals and expand access to financial services. Budiyono and Sukamulja (2023) found a direct correlation between the utilisation of mobile money and the safeguarding of digital customers. This implies that a rise in the adoption of mobile money by the working-age population in Yogyakarta's Special Region will lead to enhanced security for these clients.…”
Section: Mobile Money Services and Financial Inclusionmentioning
confidence: 92%
“…Development of airports that consider the sustainability of vulnerable groups and initiation of community development programs to empower vulnerable groups. Therefore, it is necessary to carry out careful evaluation and planning in constructing the YIA aerotropolis so that negative impacts can be minimized and positive effects can be optimized (Tari et al, 2023); (Habib et al, 2022); (Rusdiyanto et al, 2023); (Setiyaningrum & Sri Haryati, 2022); (Fadilah et al, 2021) ; (Nurul Hakim et al, 2021), (Nugroho, 2012); (Fiesta et al, 2023(Fiesta et al, ), E. F. C. S. et al,2023(Fitri & Wijaya, 2022), (Haris Farid et al, 2023) This article aims to provide an overview of the ideal aerotropolis as a recommendation for developing YIA to be as successful as aerotropolis abroad. An aerotropolis is considered good if it succeeds in creating good connectivity, generating significant economic growth, integrating infrastructure and settlements well, providing high-quality services and facilities, and applying the principles of sustainability and environmental protection.…”
Section: Introductionmentioning
confidence: 99%